2014
DOI: 10.1108/ijhcqa-11-2013-0129
|View full text |Cite
|
Sign up to set email alerts
|

Improving operating room productivity via parallel anesthesia processing

Abstract: Simulation modeling can be an effective tool to show practice change effects at a system-wide level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Similarly, surgeons who incentivized OR staff, such as providing lunch 21 also observed shorter turnovers Attending, effective communication and team work are vital to improving OR efficiency In our study anticipating and preparing for succeeding case during preceding surgery helped to improve turnover time as suggested in studies by Cendán & Good. 22 Surgeries preceded by an emergency surgery, also typically score badly.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…Similarly, surgeons who incentivized OR staff, such as providing lunch 21 also observed shorter turnovers Attending, effective communication and team work are vital to improving OR efficiency In our study anticipating and preparing for succeeding case during preceding surgery helped to improve turnover time as suggested in studies by Cendán & Good. 22 Surgeries preceded by an emergency surgery, also typically score badly.…”
supporting
confidence: 48%
“…20 Short preoperative briefings decrease the frequency of communication breakdowns. 20 Turnover time, is influenced by patient comorbidities (ASA class), preceding surgery, succeeding surgery, time of surgery, and order of OR cases 21 . ASA Class 1 and Class 2 patients had significantly shorter turnover times than ASA Class 3 patients 21 .…”
mentioning
confidence: 99%
“…9 These include the utilization of block rooms for regional anesthesia administration, dedicated orthopedic teams, parallel processing, availability of senior anesthesia staff, adequate preoperative/postoperative staffing, adequate environmental staff, and changing the infrastructure of the OR suites. 4 Other factors that affect turnover time include variables outside the OR such as equipment failure/ sterilization and patient factors. Prior studies have also suggested that surgeon delays such as inability to find the surgeon, inadequate paperwork, or improper marking of the patient was responsible for significant operative delays.…”
Section: Discussionmentioning
confidence: 99%
“…1 OS offers potential benefits to the overall healthcare system in the form of increased patient access to specialized care, time-and cost-effectiveness of surgical care, and opportunities for trainee independence. [2][3][4][5][6] Despite these benefits, the absence of a patient's chosen attending surgeon is likely highly meaningful to patients, 7,8 and patients may also not be comfortable with trainees performing portions of the procedure. [8][9][10][11][12] These two distinct but potentially related concerns come together in the practice of OS; however, little is known about patient perceptions of this practice.…”
Section: Introductionmentioning
confidence: 99%